Quantitative Phase Prediction in Dual‐Phase High‐Entropy Alloys: Computationally Aided Parametric Approach. Issue 6 (10th April 2021) - Singh Negi, Ankit; Sourav, Ayush; Heilmaier, Martin; Biswas, Somjeet; Thangaraju, Shanmugasundaram
Abstract : Dual‐phase high‐entropy alloys (HEAs) have shown remarkable mechanical properties. However, type and fraction of the secondary phase play a significant role in determining their physical and mechanical properties. CALPHAD is generally used to predict the phases and their fraction in HEAs. Herein, a parameter‐based empirical model is used to predict the phase fraction in dual‐phase HEAs. Valence electron concentration and various measures of atomic size mismatch are utilized for that purpose. A new parameter, namely, critical mismatch factor ( δ C ), is proposed in this work. Experimental verification is done on a series of Al x CoCrFeNi ( x  = 0.3, 0.5, 0.7) alloys synthesized by vacuum arc melting. Phase fraction is determined by X‐ray diffraction and electron backscatter diffraction analysis. The experimentally determined volume fraction of BCC phase in Al0.3, Al0.5, and Al0.7 is 0%, 6%, and 28–37%, respectively, which agrees closely with the predicted values proving the chosen approach useful. Abstract : A new computationally aided empirical model to predict phase fraction in high‐entropy alloy is proposed. A new parameter, critical mismatch factor ( δ c ), is introduced. The prediction accuracy of this model is 85%. This approach can predict phase fraction of any FCC/BCC‐based dual‐phase high‐entropy alloys.